STATUS HUKUM ANAK HASIL PERNIKAHAN SIRRI DAN AKIBAT HUKUMNYA - Arif Hariyanto; Ach. Azaim Ibrahimy (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2025)
An unofficial marriage is a marriage that fulfills all the pillars and requirements stipulated by Islamic law (fiqh) but is not officially registered with the authorized authorities as stipulated in applicable laws and regulations. Such a marriage is valid only according to religion, but does not align with the Prophet's Hadith, which instructs those marrying to announce their marriage at a wedding reception (feast/tasyakuran). An unofficial marriage is usually performed in the presence of a religious leader (ustad) or community leader as the registrar, or is conducted solely based on customary law. Although the marriage is considered valid under religious law, because it is not legally valid, an unofficial marriage, or an unofficial marriage, has no legal force. Therefore, an unofficial marriage is inherently detrimental and can have negative consequences for those who enter into it, especially for wives and women in general, including for children born from the unofficial marriage.